Novel species of Alternaria section Nimbya from Iran as revealed by morphological and molecular data. (3rd September 2021) - Ahmadpour, Abdollah; Ghosta, Youbert; Poursafar, Alireza
ABSTRACT: In this study, the diversity of Alternaria species in section Nimbya associated with symptomatic plants in the Cyperaceae and Juncaceae families was assessed. Multilocus sequence analyses of the rDNA internal transcribed spacer (ITS) region and parts of Alternaria major allergen ( Alt a 1 ), glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ), second largest subunit of RNA polymerase II ( RPB2 ), and translation elongation factor 1-alpha ( TEF1 ) genes revealed the presence of two previously known species, A. scirpivora and A. caricicola, and three new species, which are described here as A. cypericola, sp. nov., A. heyranica, sp. nov., and A. junci-acuti, sp. nov. These new species were characterized morphologically with respect to the dimensions of conidia, the number of pseudosepta in mature conidia, and the type of conidium apical beak. According to the results of phylogenetic analyses, the presence of long, filiform true beak is not a reliable morphological indicator for grouping species in sections Alternantherae and Nimbya and phylogenetic species recognition should be used. All identified species were described, illustrated, and their morphology and phylogenetic relationships with other species in Alternaria section Nimbya were discussed.